2006
DOI: 10.1073/pnas.0603534103
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative exploration of the occurrence of lateral gene transfer by using nitrogen fixation genes as a case study

Abstract: Lateral gene transfer (LGT) is now accepted as an important factor in the evolution of prokaryotes. Establishment of the occurrence ofLGT is typically attempted by a variety of methods that includes the comparison of reconstructed phylogenetic trees, the search for unusual GC composition or codon usage within a genome, and identification of similarities between distant species as determined by best BLAST hits. We explore quantitative assessments of these strategies to study the prokaryotic trait of nitrogen fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Because nitrogen fixation is maintained in Bacteria and Archaea, it is often hypothesized that nif genes may originate from the last common ancestor, even though other scenarios are proposed (40,41). It can be presumed that nif genes were lost in most lineages of Bacteria and Archaea and that lateral gene transfer played a role in recent acquisition of nif genes in some lineages (16,42). The rareness of nitrogen fixation properties in true Pseudomonas suggests that nif genes were lost during evolution in most (if not all) Pseudomonas species.…”
Section: Discussionmentioning
confidence: 99%
“…Because nitrogen fixation is maintained in Bacteria and Archaea, it is often hypothesized that nif genes may originate from the last common ancestor, even though other scenarios are proposed (40,41). It can be presumed that nif genes were lost in most lineages of Bacteria and Archaea and that lateral gene transfer played a role in recent acquisition of nif genes in some lineages (16,42). The rareness of nitrogen fixation properties in true Pseudomonas suggests that nif genes were lost during evolution in most (if not all) Pseudomonas species.…”
Section: Discussionmentioning
confidence: 99%
“…Even some of the molecular components of methanogens seem to have been laterally transferred to methane-oxidizing members of the domain Bacteria (33). Nitrogenases appear to have been transferred to oxygenic photosynthetic cyanobacteria late in their evolutionary history, probably from an Archaean source (34), and are widespread among diverse groups of Bacteria and Archaea (35). Ammonia monooxygenase genes that encode the key enzyme required for the oxidation of ammonia to hydroxylamine, a key step of the nitrogen cycle, are also widely distributed (36,37).…”
Section: Modes Of Evolutionmentioning
confidence: 99%
“…NifH genes are present in a broad spectrum of prokaryotes, and the phylogenetic relationships among these organisms based on nifH sequences are largely congruent with those determined from 16S rRNA gene sequences (Zehr et al 2003b). This suggests that horizontal gene transfer of the nifH gene has been limited (Zehr et al 2003b), although it has been observed for several bacterial species (Raymond et al 2004, Kechris et al 2006, Bolhuis et al 2010. Consequently, nifH sequences are used to tentatively infer phylogenetic affiliations of diazotrophs in microbial communities.…”
Section: Nitrogenase Genes From Non-cyanobacteria Are Widespread In Mmentioning
confidence: 99%